Fifty years of the bottleneck model: A bibliometric review and future research directions - Li, Zhi-Chun; Huang, Hai-Jun; Yang, Hai (Transportation research. Part B: methodological, 2020)
•Provide a 50th anniversary bibliometric review of the bottleneck model research;.•Identify influential papers, top contributing authors and leading topics;.•Review the studies in terms of travel behavior, demand-side and supply-side strategies;.•Discuss potential directions for further studies. The bottleneck model introduced by Vickrey in 1969 has been recognized as a benchmark representation of the peak-period traffic congestion due to its ability to capture the essence of congestion dynamics in a simple and tractable way. This paper aims to provide a 50th anniversary review of the bottleneck model research since its inception. A bibliometric analysis approach is adopted for identifying the distribution of all journal publications, influential papers, top contributing authors, and leading topics in the past half century. The literature is classified according to recurring themes into travel behavior analysis, demand-side strategies, supply-side strategies, and joint strategies of demand and supply sides. For each theme, typical extended models developed to date are surveyed. Some potential directions for further studies are discussed.